KARL MAYER (TO 200TH ANNIVERSARY OF HISTOLOGY TERM) - Lutsyk, O.D.; Tchaikovskyi, Yu.B. (World of Medicine and Biology, 2019)
A biographical sketch in honor of Professor Karl Mayer, who 200 years ago – in 1819 – proposed and implemented into a biomedical lexicon term «Histology».